Cognitive and Neuropsychological Assessments for Co-Occurring Opioid and Amphetamine-Type stimulant (COATS) Dependent Patients - Hashim, Norhamizah; Mohd-Zaharim, Norzarina; Weng, Tink Chooi (School of Social Sciences, 2015)
Introduction: Several studies have shown that individuals with drug dependence have poorer cognitive functioning in the domain of executive functions. Studies investigating cognitive impairments in people with poly-drug use are limited. This study is designed to assess executive functions of patients with dual drug dependence (DDD) on opioid and (Amphetamine-Type Stimulants) ATS entering medication-assisted-treatment at Hospital Universiti Sains Malaysia. Methodology: A total of n=96 male respondents (n=56 patients, and n=40 control group) were recruited for this cross-sectional study. Six neuropsychological tests (Rey-Osterrieth Complex Figure, Trail Making Test, Raven’s Progressive Matrices, Digit Span Test, Digit Symbol Test, and Stroop Test) were administered. Findings: Results showed patients performed significantly worse in perceptual motor speed, and visual scanning measured by Trail Making Test Part A, cognitive flexibility measured by Trail Making Test Part B, mental processing speed measured by Digit Symbol Test, and response inhibition measured by Stroop Test, compared to those in the control group. Conclusion: Results suggests that perceptual motor speed, visual scanning, cognitive flexibility, mental processing speed, and response inhibition may be impaired in patients with dual drug dependence. Proper prevention and treatment interventions should consider addressing cognitive deficits for patients with dual dependence